2012
DOI: 10.1111/j.1471-4159.2012.07754.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin protects neurons against amyloid beta‐peptide toxicity and ischemic stroke by attenuating multiple cell death pathways

Abstract: J. Neurochem. (2012) 122, 321–332. Abstract Intravenous immunoglobulin (IVIg) preparations obtained by fractionating blood plasma, are increasingly being used increasingly as an effective therapeutic agent in treatment of several inflammatory diseases. Its use as a potential therapeutic agent for treatment of stroke and Alzheimer’s disease has been proposed, but little is known about the neuroprotective mechanisms of IVIg. In this study, we investigated the effect of IVIg on downstream signaling pathways that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 47 publications
2
52
0
Order By: Relevance
“…We have recently shown that IVIg can be a potent neuroprotective therapy Widiapradja et al, 2012), so our next aim was to assess its effect on LRP1 in primary neurons. While it did not affect the expression levels of LRP1 under normal conditions and after 6 hours of OGD ( Fig.…”
Section: Ivig Treatment Restores the Decline In Lrp1 Levels And Phospmentioning
confidence: 99%
See 3 more Smart Citations
“…We have recently shown that IVIg can be a potent neuroprotective therapy Widiapradja et al, 2012), so our next aim was to assess its effect on LRP1 in primary neurons. While it did not affect the expression levels of LRP1 under normal conditions and after 6 hours of OGD ( Fig.…”
Section: Ivig Treatment Restores the Decline In Lrp1 Levels And Phospmentioning
confidence: 99%
“…The activation of NF-B, p38 MAPK and JNK pathways is key to ischemiainduced cellular stress responses and neuronal death Arumugam et al 2011;Widiapradja et al, 2012). Under this premise, we measured the levels and phosphorylation of NF-B-p65, p38 MAPK and JNK in RAP-treated primary neurons subjected to OGD with or without IVIg, to assess the interplay between LRP1 and IVIg pathways.…”
Section: Ivig Plays a Part In The Effect Of Lrp1 Antagonism On Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…IVIG were also found to be beneficial when used in a neuronal I/R model, inhibiting toll-like receptor-mediated responses and complement-mediated neuronal cell death [25, 26]. IVIG were also found to protect neurons against ischemic stroke via a pathway involving a reduction of caspase-3 cleavage and an elevation of the levels of the anti-apoptotic protein Bcl2 in cortical neurons [27]. …”
Section: Introductionmentioning
confidence: 99%